The Intracavitary ECG Method for Insertion of a Tunneled Dialysis Catheter without using Fluoroscopy. Issue 4 (July 2015) - Cho, Seong; Lee, Yu-Ji; Kim, Sung-Rok
Purpose: Recently, there have been many reports that exact central vein catheter tip positioning was possible using intracardiac electrocardiographic (ECG) monitoring. Ultrasonic guidance in combination with intracardiac ECG monitoring may allow for a tunneled dialysis catheter to be inserted at the bedside without using fluoroscopy. Therefore we report on the intracavitary ECG method for insertion of a tunneled dialysis catheter with ultrasound guidance and the feasibility, safety, effectiveness, complications and limitations of this method. Methods: From April 2012 to June 2014, we evaluated 142 hemodialysis (HD) patients who were dialyzed by a tunneled dialysis catheter that was inserted using intracardiac ECG monitoring without fluoroscopic usage. We checked the intracardiac P wave and the point at which it gradually rose to the highest P wave morphology, we stopped inserting the catheter. Results: Catheter flow during dialysis was adequate in 139 cases. There were three cases where it malfunctioned. Catheter malposition occurred in 6 out of 142 cases. The correct matching rate between the intracardiac ECG and chest posteroanterior (PA) view was 98.5%. No significant complications developed. Conclusions: To conclude, in this single-center study, the intracavitary ECG method for assessing the position of the tip of tunneled dialysis catheter was proven to be safe and feasible in virtually all adult patients who had an evident P wave at the basal ECG tracking.